PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS X DALAM MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMK NEGERI 2 TONDANO - Geofani Saul Darius Runtukahu; Sylvia Jane Annatje Sumarauw; Cori Pitoy (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine whether the application of the Project Based Learning (PjBL) learning model will improve the learning outcomes of class X students of SMK Negeri 2 Tondano in the matter of the linear equation system with two variables (SLPDV). The type of research used in this study was a quasi experiment with a posttest only control group design. This research was conducted at SMK Negeri 2 Tondano, class X MPLB 2 as the control class and X MPLB 3 as the experimental class. The results showed that the average learning outcomes of the experimental class with the implementation of the PjBL model was 76.21 while the average learning outcomes of students in the control class with the implementation of the conventional model were 54.63 through the administration of the final test (posttest). Because the significant value is lower than 0.05 (0.000 <0.05) then H0 is rejected and H1 is accepted, namely the average learning outcomes of students who study using the PjBL learning model are higher than the learning outcomes of students who study using conventional models. This means that the PjBL learning model can improve student learning outcomes in class X SPLDV material